Β-Xylopyranosides: synthesis and applications. Issue 110 (29th October 2015) - Brusa, Charlotte; Muzard, Murielle; Rémond, Caroline; Plantier-Royon, Richard
Abstract : In recent years, β-xylopyranosides have attracted interest due to the development of biomass-derived molecules. This review focuses on general routes for the preparation of β-xylopyranosides by chemical and enzymatic pathways and their main uses. Abstract : d -Xylose is the main constituent of hemicelluloses, the second most abundant polysaccharide in nature after cellulose. Thus, the β-xylopyranose motif is widely distributed in the plant kingdom. On the contrary, d -xylose is an unusual carbohydrate in mammalian cells, only present in the structures of proteoglycans, macromolecules with important biological functions. In recent years, β-xylopyranosides have attracted renewed interest due to the development of biomass-derived molecules and their numerous applications. In this review, we will first focus on general routes for the preparation of β-xylopyranosides according to the nature of the glycosidic linkage and the aglycone moiety by chemical and enzymatic pathways. The main uses of these molecules for different applications, such as activators in the biosynthesis of glycosaminoglycans, for enzyme inhibition and as surfactants will be presented.